The Performance of the Modified GCC Technique for Differential Time Delay Estimation in the Cooperative Sensor Network - Velickovic, Z. S.; Pavlovic, V. D. (Elektronika ir Elektrotechnika, 2013)
In this paper, a modified GCC technique (or FPT) for time delay estimation (TDE) is described. A flipped parameter (FP) can be defined for any sensor and is estimated during the observation period. Unlike classical TDE methods that evaluate the cross-correlation function, FPT requires flipped correlation evaluation based on each single sensor signal. The proposed technique gives accurate results for both coherent and non-coherent signals with symmetrical spectrum around the central frequency. The use of FPT method is especially significant for distributed sensor networks. The main features of the FPT are tested in a noisy simulation environment and the results are compared with classical methods. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.2445